Helmintíase intestinal afeta negativamente a resposta celular específica contra o Mycobacterium tuberculosis em pacientes co-infectados - Goulart, Juliana Silva Pancini (2009)
The protection against Mycobacterium tuberculosis (MTB) depends on a cellmediated Th1 type-immune response. This response is characterized by IFN-g production by CD4+ T cells, which activates macrophages to enhance microbicidal mechanisms leading to the bacillus eradication. Factors related to tuberculosis resistance or susceptibility are not completely understood. There are evidences suggesting that the progress to active disease is related to immune downregulation caused by suppressors cytokines and regulatory T cells. It is believed that the association with helminth infection can disturb the protective immune response that should contain or eliminate MTB. Here, we investigated the role of intestinal helminth infection on M. tuberculosis specific immune response during active pulmonar tuberculosis in patients with associated tuberculosis and intestinal helminth infection at the time of diagnosis and during tuberculosis therapy. Quantitative and phenotypic analyses of peripheral blood cells populations were performed and the MTBstimulated whole blood culture cytokines production was evaluated. Fifty-three patients with newly diagnosed tuberculosis were enrolled for this study. Twenty-six percent of these patients were infected with at least one intestinal helminth (TB + HELM patients). Patients with pulmonary tuberculosis presented a significant reduction in the numbers of TCD8+, NK and NKT cells. Patients with both intestinal helminth infection and tuberculosis presented higher frequency of regulatory T cells, of both phenotype CD4+CD25HIGH and CD4+CD25HIGHFoxp3+, as compared to TB group, to HELM group, and to control group. In addition, the results suggest a hipoergy status in TB + HELM patients because the production of the cytokines IL-2, TNF-a, IL-4, IL-5 and IL-10 decreased in whole blood culture of these patients as compared to both TB patients and healthy controls. The data from this study indicated that the associated intestinal helminth infection has a negative impact on immunity to tuberculosis in patients with tuberculosis.